Staging the Feminine Ethic of Care: A Review of Reimagining the Academy - Zavros-Orr, Agli (Art/Research International, 2022)
The neoliberal university can be a restrictive, repressive, and/or oppressive space. However, the contributions in this edited publication “Reimagining the Academy: ShiFting towards Kindness, Connection, and an Ethics of Care” by Alison L Black and Rachael Dwyer and published by Palgrave Macmillan represent hope, kindness, love, and compassion. The words and works contained in this book gift to any reader many enriching, impactful storied accounts of academic works from differentiated perspectives. These important works support the re-imagining of academic spaces, scholarship, research, teaching and learning and care for self, others, and the work that matters. My reading of these works engaged my individuated ethic of care and inspired a creative response – artistic and poetic storying as an act of performative synthesis of the experience that awaits the reader.